Sirkulasi Virus Flu Burung Subtipe H5 pada Unggas di Jawa Barat, Banten, dan Jawa Timur Sepanjang Tahun 2008-2009 (CIRCULATION OF AVIAN INFLUENZA OF H5 SUBTYPE ON BIRDS IN WEST JAVA, BANTEN AND EAST JAVA DURING 2008-2009) - Dyah Ayu Hewajuli; Ni Luh Putu Indi Dharmayanti (Faculty of Veterinary Medicine, Udayana University and Published in collaboration with the Indonesia Veterinarian Association, 2012)
The epidemic of avian influenza (AI) in Indonesia initially occurred at the end of 2003 which caused100% death of the affected chickens. It was caused by avian influenza virus (AIV) subtype H5. Recent datashowed that highly pathogenic avian influenza (HPAI)-H5N1 virus is still endemic among bird populationin Indonesia. A study was therefore conducted to find out the distribution of AIV-H5N1 in several regionsin Indonesia. Reverse transcriptase-polymerase chain reaction (RT-PCR) was used to detect the presenceof AI-H5 virus and hemagglutination inhibition (HI) test was used to detect the presence of anti-AIV-H5antibody. Results showed that anti-AIV-H5 antibody was detected in 36 % and was not detected in 64% oftested birds in West Java, Banten and East Java. The AIV-H5 antibody titer varied from low to high titer.The AIV-H5 was detected in samples from Cianjur (30%), Blitar (1.9&), Serang (12.5%) and pandeglang(17.5%). It was evident that AIV-H5 is still endemic in Indonesia.